Steps towards a Phenomenology of Video Games—Some Thoughts on Analyzing Aesthetics and Experience - Bakels, Jan-Hendrik (Eludamos: Journal for Computer Game Culture, 2021)
This paper aims at conceiving a heuristic framework for analyzing video game aesthetics as well as the ways in which these aesthetics are experienced. As the main point of departure for the thoughts laid out throughout the article, I turn to phenomenological contributions to film, media and game studies—with a special emphasis on approaches to kinaesthesia. After discussing essential papers on the kinaesthetic experience of playing video games as well as drawing on a phenomenological approach to the intersubjective sharing of affects by means of kinaesthesia conceived within the field of developmental psychology, I turn to a series of brief game-analytical sketches that are supposed to highlight certain aspects of experiencing time, space, and materiality while playing video games. Finally, the specific quality of interactive intersubjectivity in video gaming is discussed, resulting in the introduction of the theoretical concept of auto-affectivity.